Efektivitas Penggunaan QRIS Sebagai Alat Transaksi Digital Di Kota Bima - Puji Muniarty; M Syukur Dwiriansyah; Wulandari Wulandari; M Rimawan; Ovriyadin Ovriyadin (Owner : Riset dan Jurnal Akuntansi, 2023)
Various innovations from today's technological developments continue to diversify in various implementations, especially in the economic sector. Almost all activities in the digitalized era are fast, accurate and efficient. The role of the internet attracts some business actors to switch from traditional business models to online business-based business models as well as inventory with information or physical goods that are modified with electronic products that utilize digital marketing that uses digital technology that has been integrated with new technologies such as smartphones and their supporting applications. . The research objective is to measure the effectiveness of using QRIS as a digital transaction tool in the City of Bima. This type of research is qualitative with purposive sampling. The research sample is millennial generation students who always use QRIS as a means of payment in buying various products or services both online and offline. Interview data collection techniques and literature study. From the results of the interviews it was found that students as a mineral generation did not feel that they were using QRIS in Kota Bima, that in terms of the ease and benefits of using QRIS it was effective, this reflected the results of interviews with informants who stated that they did not find difficulties in using QRIS and even using QRIS made it easier for them to do so. purchase and payment transactions for products/services both online and offline.